How executives talk: Exploring marketing executive value articulation with computerized text analysis. (6th February 2020) - Key, Thomas Martin; Keel, Astrid Lei
Abstract : Purpose: This paper aims to explore how chief executive officers (CEOs) and C-suite marketing executives (chief marketing officers [CMOs], chief customer officers [CCOs], chief branding officers [CBOs], etc.) talk about marketing concepts to better understand how marketers can more effectively articulate their value and increase their strategic influence within the firm. Design/methodology/approach: Artificial intelligence-enabled computerized text analysis was used to identify and weight keywords from 266 CEO and C-suite marketing executive interviews. Custom marketing concept dictionaries were used to gauge overall marketing focus. Findings: The analysis revealed opportunities for C-suite marketers to align specific marketing concepts with that of CEOs for increased strategic influence. Comparisons between C-suite marketing roles showed that CMOs are more focused on marketing strategy than specialized C-suite marketing positions, such as CCO and CBO. This points to a potential decrease in strategic impact for marketing executives dependent on the specialization of their position. Research limitations/implications: Using IBM Watson's black-box artificial intelligence may limit the ability to replicate results from the content analysis; however, the results identify important ways that marketing executives can use to increase their ability to articulate their value within the firm. Practical implications: C-suite marketing executives who want to increase the strategic alignment of their role with their firm must pay close attention to the marketing concepts they talk about, and how those align with their CEO's marketing knowledge. The creation of specialized C-suite marketing roles may unintentionally limit the strategic thinking and firm-level impact of marketers. Originality/value: This paper represents the first use of artificial intelligence-enabled computerized text analysis to explore and compare executive speech acts to help increase marketing's influence in the firm. It is also the first to explore differences in marketing concept use between C-suite marketing roles.